The Relevance of Jungian Psychological Theory towards the Analysis of Housewifization Representations in Photojournalism - Prastiti, Ni Putu Suci; Artayasa , I Nyoman (Journal of Aesthetics, Creativity and Art Management, 2025)
Mass media play a significant role in shaping public perception of various aspects of life, including gender roles within households. One intriguing aspect in this context is the representation of housewives in photojournalism. This phenomenon often emerges through what is known as housewifization, the process by which the role of housewives is reduced to narrow stereotypes confined solely to domestic affairs. This writing aims to explore how Carl Gustav Jung's Jungian psychology approach can be applied to analyze the representation of mother subjects in news media. The research method used is descriptive qualitative. The results of this study indicate that Jungian psychological analysis offers an intriguing approach to understanding the phenomenon of housewifization in the context of photojournalism. This paper hopes to provide new insights into how media shape our perceptions of gender roles in society and pave the way for deeper reflection on the cultural and psychological implications of this phenomenon.